2011
DOI: 10.1111/j.1472-765x.2011.03110.x
|View full text |Cite
|
Sign up to set email alerts
|

Metal-ion susceptibility of oral bacterial species

Abstract: Summary Aims:  This study aimed to evaluate the effect of lead (Pb) on growth of bacterial species related to dental diseases in vitro. Methods and Results:  The effects of lead acetate on representative species of the oral flora were examined at 0·1–10 mmol l−1 and compared with the effect of silver nitrate and ferrous sulfate. The minimal inhibitory concentration of lead acetate was between 0·15 and 5 mmol l−1 for the bacterial strains tested. The minimal bactericidal concentration of lead acetate for most o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 30 publications
1
15
1
Order By: Relevance
“…MIC values for AgNO 3 have not been previously reported for saline–BHI media, but the value here is much lower than those reported in other growth media for S. mutans (e.g., 20 mg l −1 in tryptone–glucose–Marmite medium, 24 h incubation time, Thibodeau et al 1978; 100 mg l −1 in basal medium, 24 h incubation time, Youravong et al 2011), suggesting that Ag was more bioavailable in the media used in the present study. Reports of MIC values for 24 h exposures of S. mutans to sub-100 nm-sized Ag NPs also vary (e.g., 67 mg l −1 , particles size: 9 nm, S. mutans inoculum: 6 × 10 5 CFU/ml −1 in BHI + 2% sucrose, Espinosa-Cristobal et al 2009; 4.9 ± 2.7 mg l −1 , particle size: 25 nm, S. mutans inoculum: 1.5 × 10 5 CFU/ml −1 in saline–phosphate buffer solution, Hernandez-Sierra et al 2008).…”
Section: Discussioncontrasting
confidence: 76%
“…MIC values for AgNO 3 have not been previously reported for saline–BHI media, but the value here is much lower than those reported in other growth media for S. mutans (e.g., 20 mg l −1 in tryptone–glucose–Marmite medium, 24 h incubation time, Thibodeau et al 1978; 100 mg l −1 in basal medium, 24 h incubation time, Youravong et al 2011), suggesting that Ag was more bioavailable in the media used in the present study. Reports of MIC values for 24 h exposures of S. mutans to sub-100 nm-sized Ag NPs also vary (e.g., 67 mg l −1 , particles size: 9 nm, S. mutans inoculum: 6 × 10 5 CFU/ml −1 in BHI + 2% sucrose, Espinosa-Cristobal et al 2009; 4.9 ± 2.7 mg l −1 , particle size: 25 nm, S. mutans inoculum: 1.5 × 10 5 CFU/ml −1 in saline–phosphate buffer solution, Hernandez-Sierra et al 2008).…”
Section: Discussioncontrasting
confidence: 76%
“…Silver is a broad-spectrum chemical with excellent anti-biofilm properties, and hence widely integrated into indwelling devices such as orthopedic prostheses, cardiac devices, and surgical instruments [16][17][18]. In dentistry too, the susceptibility of several species of oral microbiota to silver-ions has been reported [19,20], as a result of which it is now incorporated into some dental materials [21]. The exact mechanisms by which particulate silver kills bacteria and fungi are unclear, but it is known that silver causes microbial death by binding to microbial cell wall and membrane components thus causing toxicity and death of the organisms [22].…”
mentioning
confidence: 99%
“…Although this association was only marginally significant (P = 0.06), this is probably because the PbS concentrations were not high enough to inhibit oral bacterial species. In a recent in vitro study, Youravong et al 38 reported minimal inhibitory concentrations (MICs) of lead on oral bacteria in the range of 0.15-5 mM and minimal bactericidal concentrations (MBCs) in the range of 5-10 mM. The MIC and MBC values of mutans streptococci were 2.5 mM and 10 mM respectively, while the MBC of L. acidophilus was 5 mM.…”
Section: Discussionmentioning
confidence: 99%